2022
DOI: 10.3389/fmed.2022.911990
|View full text |Cite
|
Sign up to set email alerts
|

Retinal and choroidal microvascular alterations in Behcet’s disease without ocular manifestations: A systematic review and meta-analysis

Abstract: PurposeWe performed a systematic review and meta-analysis to examine the microvascular alterations in non-ocular Behcet’s disease (BD) using optical coherence tomography angiography (OCTA).MethodsA comprehensive search was performed in Pubmed, Embase and Cochrane databases for eligible studies from inception to February 2022. Detailed clinical demographics were extracted from each study by two independent reviewers. The weighted mean difference (WMD) and 95% confidence intervals (CI) were used to compare the O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Therefore, OCT-A cannot replace FA in monitoring BD uveitis. Nevertheless, several OCT-A studies have been recently published, suggesting its use as an adjunctive imaging modality in BD uveitis [35–38]. In a meta-analysis of cross-sectional studies comparing OCT-A findings between BD patients without ocular involvement and healthy controls, a significantly lower parafoveal capillary density and a larger foveal avascular zone (FAZ) have been reported in BD patients [35].…”
Section: Assessment Of Disease Activity and Imaging Studies In Behçet...mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, OCT-A cannot replace FA in monitoring BD uveitis. Nevertheless, several OCT-A studies have been recently published, suggesting its use as an adjunctive imaging modality in BD uveitis [35–38]. In a meta-analysis of cross-sectional studies comparing OCT-A findings between BD patients without ocular involvement and healthy controls, a significantly lower parafoveal capillary density and a larger foveal avascular zone (FAZ) have been reported in BD patients [35].…”
Section: Assessment Of Disease Activity and Imaging Studies In Behçet...mentioning
confidence: 99%
“…Nevertheless, several OCT-A studies have been recently published, suggesting its use as an adjunctive imaging modality in BD uveitis [35–38]. In a meta-analysis of cross-sectional studies comparing OCT-A findings between BD patients without ocular involvement and healthy controls, a significantly lower parafoveal capillary density and a larger foveal avascular zone (FAZ) have been reported in BD patients [35]. In another meta-analysis of OCT-A studies including BD patients with or without ocular involvement, the authors reported a high heterogeneity of results; yet pooled data showed significantly lower vessel densities in both superficial and deep parafoveal capillary plexus as well as enlarged FAZ in BD patients with ocular involvement and similar findings also in those without [36].…”
Section: Assessment Of Disease Activity and Imaging Studies In Behçet...mentioning
confidence: 99%